Krzysztof Czyżewski a paryska „Kultura” - Wal, Anna (Tematy i Konteksty, 2019)
The paper focuses on the various forms of collaboration of Krzysztof Czyżewski, the founder of the Borderland Foundation in Sejny, organiser of cultural events, poet and essayist, with Parisian Kultura. It discusses Czyżewski’s essays, published in the magazine between 1997-2000 which concerned the problems of Central and Eastern Europe and the issues connected with the borderland. The paper points to the idea, emphasized by Czyżewski, of multicultural dialogue and building open societies in the multicultural regions of Central and Eastern Europe after 1989 based on historical memory while at the same time overcoming the existing conflicts. It mentions the prizes awarded to Czyżewski by Jerzy Giedroyc and the fact that he is considered the continuator of the program of Kultura, promoting the strengthening of the bonds between Poland and its closest neighbours.